1991
DOI: 10.1002/jso.2930460213
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of a solitary liver metastasis in a 46‐year‐old patient with a malignant thymoma

Abstract: Clinical history, surgical treatment, and pathologic findings of a solitary liver metastasis of a malignant thymoma in a 46-year-old female are reported. An extensive literature review has revealed no record of surgical resection of liver metastasis in a patient with invasive thymoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, some cases of hematogenous metastasis in the liver have been reported. 3 However, to our knowledge, the present report is the fi rst one that describes direct invasion of thymoma to the liver. Strobel et al 4 recently reported that, although the 5-year survival rate of stage IV thymoma was similar to that of stage III (85% and 88%), the 10-year survival rate dropped to 47%.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, some cases of hematogenous metastasis in the liver have been reported. 3 However, to our knowledge, the present report is the fi rst one that describes direct invasion of thymoma to the liver. Strobel et al 4 recently reported that, although the 5-year survival rate of stage IV thymoma was similar to that of stage III (85% and 88%), the 10-year survival rate dropped to 47%.…”
Section: Discussionmentioning
confidence: 83%
“…16 Reviewing the English literature identified fifteen cases of metastatic thymoma to the liver, 7,[16][17][18][19][20][21][22] but only in six cases was the liver the only site of extrathoracic recurrence; and detailed information was only available for four cases. 17,[19][20][21] Three case reports described metachronous single liver metastases after primary resection of the thymoma; [19][20][21] and a fourth report described a case of multiple metastatic thymoma to the liver (Table 2). 17 Neoadjuvant chemotherapy was administrated and it resulted in regression of the primary lesion, which was completely resected, and one persistent hepatic nodule was treated with radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%